2021
DOI: 10.1111/ejn.15377
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral electrical stimulations of the temporal lobe: A stereoelectroencephalography study

Abstract: The functional anatomy of the anteromesial portion of the temporal lobe and its involvement in epilepsy can be explored by means of intracerebral electrical stimulations. Here, we aimed to expand the knowledge of its physiological and pathophysiological symptoms by conducting the first large‐sample systematic analysis of 1529 electrical stimulations of this anatomical region. We retrospectively analysed all clinical manifestations induced by intracerebral electrical stimulations in 173 patients with drug‐resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…[9][10][11][12] In literature, several studies have reported visceral or emotional sensations by studying the stimulation of a single brain area such as the insula, 13,14 the cingulate cortex, 15 or the temporal lobe (especially the temporal pole and mesial temporal lobe). 16,17 In our study, we did not select a brain region, but we reported all the stimulations having evoked VES, after stimulations performed all over cortical structures. This is the first study to functionally map VES after stimulating the whole cortical mantle.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] In literature, several studies have reported visceral or emotional sensations by studying the stimulation of a single brain area such as the insula, 13,14 the cingulate cortex, 15 or the temporal lobe (especially the temporal pole and mesial temporal lobe). 16,17 In our study, we did not select a brain region, but we reported all the stimulations having evoked VES, after stimulations performed all over cortical structures. This is the first study to functionally map VES after stimulating the whole cortical mantle.…”
Section: Introductionmentioning
confidence: 99%
“…2). This problem has also been observed for DBS in MTLE patients 26,57 and we solved it by ramping up the stimulation current gradually over the first four minutes. To target the first requirement mentioned above, we implemented an online analysis script that identified epileptiform discharges from a single LFP recording electrode using a combination of spectral power and amplitude thresholds.…”
Section: Efficient Control Of Focal Seizure Clusters By On-demand Lfsmentioning
confidence: 75%
“…Additionally, recent findings demonstrated that LFS (10 min on/off) at 1 Hz in the epileptic focus decreased cortical excitability in pharmacoresistant epilepsy patients 25 . Due to the low intrinsic epileptogenic threshold of the hippocampal formation, LFS might be advantageous over HFS since it has a lower probability to elicit generalized seizures when applied in an interictal phase 26 .…”
Section: Introductionmentioning
confidence: 99%
“…The effective electrical stimulations were then classified according to the presence or absence of electrical modification on the EEG, defined as after discharge (AD). The responses to effective stimulations were classified as physiological if never experienced by the patient before and without electrical modification (Supplementary response (including complex symptom belonging to more than one of the above categories); and (xiii) unclassified response (when the effect was not possible to include in any of the above categories) (Balestrini et al, 2015;Mariani et al, 2021;Qi et al, 2022;So & Alwaki, 2018).…”
Section: Intracranial Electrical Stimulation Protocolmentioning
confidence: 99%